Home appliances-controlled platform with homekit application - Vongchumyen, Charoen; Torthitithum, Sarayuth; Khamsopa, Jirachaya; Watanachaturaporn, Pakorn (My University, 2019)
Home appliances-controlled platform with HomeKit application is a platform that allows users to control general appliances via HomeKit, which is an application from Apple on any device running iOS10 or later. The platform is the communication medium between application and appliances. The appliances do not need to be manufactured by Apple since they are expensive and have to put an effort in case the customer want to buy it. The platform is capable of receiving and transferring data to a HomeKit application for data processing, then transmits signal back to control the operation of the appliances. Within the platform, there is a section that acts as a communication server for the HomeKit application which is like a direct Apple server. In addition to receiving and sending data from the HomeKit application, the platform also has an automatic control that is controlled by the reading sensor contained in each platform comparing the threshold values, user defined. Each platform has different sensors based on their operations and can control only one type of appliance because each type of control uses different signal, the control must be unique, matching the type of appliances and the form of command in different manufacturers.
Keywords: Controlled Platform; Homekit; iOS; IoT